Maternal determinants of preterm birth at the Hospital Provincial Ginecobstétrico Fe del Valle Ramos - Elida Mendoza Jorge; Danae Cecilia Jiménez Mendoza; Lesyania Segura Linares; Yunior Meriño Pompa; Sulanys Yanet Naranjo Vázquez (Revista Información Científica)
Introduction: preterm birth care is a challenge for public health because it is a cause of neonatal mortality and morbidity.